The Watkin's dictionary of religins an secular faiths - Benedict, Gerald (London : Watkins Publishing, 2008)
Describes the major religions and belief systems as well as many of the denominations, cults, and sects that have stemmed from them.
Keywords: Religions -- Dicitonary